Satellite traces, range spread-F occurrence, and gravity wave propagation at the southern anomaly crest - Cabrera, Miguel Angel (2010)
Abstract. Range spread-F (RSF) and occurrence of "satellite" traces prior to RSF onset were studied at the southern peak of the ionospheric equatorial anomaly (EA). Ionograms recorded in September 2007 at the new ionospheric station of Tucumán, Argentina (26.9° S, 294.6° E, dip latitude 15.5° S), by the Advanced Ionospheric Sounder (AIS) developed at the Istituto Nazionale di Geofisica e Vulcanologia (INGV), were considered. Satellite traces (STs) are confirmed to be a necessary precursor to the appearance of an RSF trace on the ionograms. Moreover, an analysis of isoheight contours of electron density seems to suggest a relationship between RSF occurrence and gravity wave (GW) propagation.